2009
DOI: 10.1161/circresaha.108.191189
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Activity of Seryl-tRNA Synthetase Is Involved in Vascular Development

Abstract: Abstract-Vascular endothelial growth factor (Vegf) plays central roles in the establishment of stereotypic vascular patterning in vertebrates. However, it is not fully understood how the network of blood vessels is established and maintained during vascular development. A zebrafish ko095 mutant presented the disorganized vessels with abnormal branching of the established intersegmental vessels (ISVs) after 60 hours postfertilization. The gene responsible for ko095 encodes seryl-tRNA synthetase (Sars) with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 47 publications
5
98
0
Order By: Relevance
“…The N-terminal coiled-coil domain of SRS is unique among ARS, but similar structures are common in other nucleic acid-binding proteins (4). Whether the N-terminal domain of SRS interacts with other nucleic acids is unknown, but it has been reported that SRS plays a role during the development of zebrafish (5)(6)(7). Thus, the coiled-coil domain of SRS may be carrying out functions other than tRNA recognition.…”
mentioning
confidence: 99%
“…The N-terminal coiled-coil domain of SRS is unique among ARS, but similar structures are common in other nucleic acid-binding proteins (4). Whether the N-terminal domain of SRS interacts with other nucleic acids is unknown, but it has been reported that SRS plays a role during the development of zebrafish (5)(6)(7). Thus, the coiled-coil domain of SRS may be carrying out functions other than tRNA recognition.…”
mentioning
confidence: 99%
“…[40] Two independent forward-genetic studies in zebrafish demonstrated involvement of vertebrate SerRS in vascular development. [41,42] Random chemical mutagenesis introduced premature stop-codons within the gene for cytosolic SerRS, leading to abnormal blood vessel formation and defective blood circulation in the zebrafish embryo. The human SerRS also affects angiogenesis, and SerRS influence on vascular development is independent of its catalytic activity.…”
Section: Noncanonical Roles Of Serrsmentioning
confidence: 99%
“…The human SerRS also affects angiogenesis, and SerRS influence on vascular development is independent of its catalytic activity. [41] The noncanonical activity was linked to the dysregulation of vascular endothelial growth factor A (VEGFA) expression, a key regulator of angiogenesis and vasculogenesis. [41] The model of canonical or bacterial-type SerRS (A) and atypical or methanogenic-type SerRS (B) in complex with tRNA.…”
Section: Noncanonical Roles Of Serrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune cells inflict tumor initiation, growth and progression intervened by proinflammatory cytokines. IARS, HARS and AARS are efficiently cleaved by granzyme B, a serine protease released by cytoplasmic granules within cytotoxic T cells and natural killer, NK, cells and involved in the induction of programmed cell death in the target cell, thus eliminating cells that have become cancerous, to generate autoantigenic fragments with chemokine activity [115]. QARS, known to be an apoptosis suppressor, inhibits the pro-apoptotic signaling pathway through glutamine-dependent interaction with apoptosis signal-regulating kinase 1, ASK1, induced by heat shock, irradiation, and c-Myc overexpression.…”
Section: Hypotheses On Mechanisms Of Trn-a-rs Link To Diseases and Camentioning
confidence: 99%